Abelson tyrosine-protein kinase 2 regulates myoblast proliferation and controls muscle fiber length - Jennifer K Lee; Peter T Hallock; Steven J Burden (eLife, 2017)
Muscle fiber length is nearly uniform within a muscle but widely different among different muscles. We show that Abelson tyrosine-protein kinase 2 (Abl2) has a key role in regulating myofiber length, as a loss of Abl2 leads to excessively long myofibers in the diaphragm, intercostal and levator auris muscles but not limb muscles. Increased myofiber length is caused by enhanced myoblast proliferation, expanding the pool of myoblasts and leading to increased myoblast fusion. Abl2 acts in myoblasts, but as a consequence of expansion of the diaphragm muscle, the diaphragm central tendon is reduced in size, likely contributing to reduced stamina of Abl2 mutant mice. Ectopic muscle islands, each composed of myofibers of uniform length and orientation, form within the central tendon of Abl2+/− mice. Specialized tendon cells, resembling tendon cells at myotendinous junctions, form at the ends of these muscle islands, suggesting that myofibers induce differentiation of tendon cells, which reciprocally regulate myofiber length and orientation.